Training specialists in physical education in the system of additional education - Yuri Ya. Lobanov, Elena G. Saykina,; Smirnova, Yuliya V.; Kuz’mina, Svetlana V.; Olga N. Fedorova, Mariya A. Soldatova, (Opción, 2019)
The research considers the issues of professional retraining and advanced training of specialists in physical education for the development of innovative health-improving physical education via the longitudinal study as a method. As a result, a close correlation was discovered between the complexity of group monitoring, implementation of a student-centered approach, the difficulty of compiling sets of exercises accompanied by music, and a lack of experience. In conclusion, the modernization of the existing system of training specialists in physical education in extension and retraining courses with an emphasis on the use of innovative educational technologies is crucial.